Apakah Perusahaan dengan ESG Tinggi Memiliki Kinerja Keuangan yang Lebih Baik? - Renfiana, Lilis; Hendri, Loni; Idaman, Northa (Budgeting: Jurnal Akuntansi Syariah, 2025)
Environmental, Social, and Governance (ESG) issues have gained global prominence in sustainable investing, yet empirical evidence on their relationship with corporate profitability in emerging markets like Indonesia remains limited and inconsistent. This study examines differences in profitability, measured by Return on Assets (ROA), among companies with varying ESG performance categories on the Indonesia Stock Exchange. A comparative quantitative method was applied to a sample of 84 companies classified into three ESG categories (Good, Medium, Poor) based on Sustainalytics scores. Data analysis employed descriptive statistics, Shapiro-Wilk normality test, and the non-parametric Kruskal-Wallis test. The results revealed no statistically significant differences in ROA among the three ESG groups (H = 4.452, p = 0.108). An interesting finding emerged from the numerical pattern showing the "Poor" ESG group achieved the highest average ROA (6.38%), followed by the "Medium" (4.99%) and "Good" (4.75%) groups. This study concludes that no significant relationship exists between ESG performance and short-term profitability in the context of Indonesia's capital market. The research implications highlight the importance of long-term perspectives in ESG integration and the need for strategic approaches that consider the specific characteristics of emerging markets.